Oct4-mediated reprogramming induces embryonic-like microRNA expression signatures in human fibroblasts - Peskova, Lucie; Cerna, Katerina; Oppelt, Jan; Mraz, Marek; Barta, Tomas (Scientific reports, 2019)
Oct4-mediated reprogramming has recently become a novel tool for the generation of various cell types from differentiated somatic cells. Although molecular mechanisms underlying this process are unknown, it is well documented that cells over-expressing Oct4 undergo transition from differentiated state into plastic state. This transition is associated with the acquisition of stem cells properties leading to epigenetically "open" state that is permissive to cell fate switch upon external stimuli. In order to contribute to our understanding of molecular mechanisms driving this process, we characterised human fibroblasts over-expressing Oct4 and performed comprehensive small-RNAseq analysis. Our analyses revealed new interesting aspects of Oct4-mediated cell plasticity induction. Cells over-expressing Oct4 lose their cell identity demonstrated by down-regulation of fibroblast-specific genes and up-regulation of epithelial genes. Interestingly, this process is associated with microRNA expression profile that is similar to microRNA profiles typically found in pluripotent stem cells. We also provide extensive network of microRNA families and clusters allowing us to precisely determine the miRNAome associated with the acquisition of Oct4-induced transient plastic state. Our data expands current knowledge of microRNA and their implications in cell fate alterations and contributing to understanding molecular mechanisms underlying it.
Keywords: Cell Line; MicroRNAs; regulace genové exprese; lidé; Gene Expression Regulation; buněčné linie; Cellular Reprogramming Techniques; Octamer Transcription Factor-3; techniky buněčného přeprogramování; oktamerní transkripční faktor 3; Embryo, Mammalian; embryo savčí; fibroblasty; mikro RNA; Fibroblasts; Humans